La « Nouvelle Mosquée » d’Alger. Le déroulement d’une procédure constructive au xviie siècle - Samia Chergui (Revue des Mondes Musulmans et de la Méditerranée)
The "New Mosque" was built in the late seventeenth century for the sole purpose of providing Hanafi rite Muslims their own Great Mosque. The new building was clearly the result of an exceptional collective course of action, undertaken by the Algiers militia, in this case the Janissary corps, with funds from Subul al-Khayrat. A review of the accounting books of the h.abus, the institution responsible for managing most Hanefi mosques and Awqâf, has allowed us to track the work progress over a period of almost ten years, from 1067/1656-1657 to 1076/1665-1666. The records of the construction site provide significant insights into the nature, origin, quantity and cost of materials used in construction. They also provide information on their fabrication, preparation, and occasionally, their implementation, an implementation which is based on the dexterity of many men, part of a corporate structure. The project’s payroll accounts are one of the few management records that, for at least a decade, provide detailed individual profiles of all stakeholders as well as their geographical origins and even their faiths.